Given the function f ( x ) = − 1 x + 3 x 4 , f(x)=− x 1 ​ + 4 3 x ​ ​ , find f ′ ( 4 ) . f ′ (4). Express your answer as a single fraction in simplest form.

Respuesta :

Step-by-step explanation:

The question is not well written. Let us say the function given as expressed as;

f(x) = -1/x + 3/x⁴

f'(x) means we are to differentiate the function with respect to x;

Given f(x) = axⁿ

f'(x) = naxⁿ⁻¹

f(x) = -x⁻¹ + 3x⁻⁴

Applying the differentiation formula we will have;

f'(x) = -1(-x⁻²)+(-4)3x⁻⁴⁻¹

f'(x) = x⁻²-12x⁻⁵

Express as a fraction

f'(x) = 1/x²-12/x⁵

To get f'(4), we will have to substitute x = 4 into the resulting expression

f'(4) = 1/4²-12/4(5)

f'(4) = 1/16-12/20

f'(4) = 1/16-3/5

Find the LCM

f'(4) = (5-48)/80

f'(4) = -43/80

Note that the function used was assumed but the same method can be employed to any other functions.